Skogen som alternativ till privat pensionssparande - Werner, Andreas (SLU/School for Forest Management, 2016)
The possibilities of saving money for retirement in banks and insurance companies are plenty. Possibilities of making tax deductions for private retirement savings are from year 2016 gone, which leads common people to look for other ways of saving or invest their money. The purpose of this report is to compare yield from investments in forestland, condominiums, shares, bonds and fixed income securities. The studies will result in: